Incorporating the Concept of Relevance in Clinical Rehabilitation Research and Its Reviews May Improve Uptake by Stakeholders. (18th August 2022) - Pomeroy, J. Mary Louise; Sanchez, Jonathan O.; Cai, Cindy; Garfinkel, Steven; Côté, Pierre; Frontera, Walter R.; Gerber, Lynn H.
Abstract: The "relevance" of research to stakeholders is an important factor in influencing the uptake of new knowledge into practice; however, this concept is neither well defined nor routinely incorporated in clinical rehabilitation research. Developing a uniform definition, measurement standards, stakeholder engagement strategies, and guiding frameworks that bolster relevance may help incorporate the concept as a key element in research planning and design. This article presents a conceptual argument for why relevance matters, proposes a working definition, and suggests strategies for operationalizing the construct in the context of clinical rehabilitation research. We place special emphasis on the importance of promoting relevance to patients, caregivers, and clinicians and provide preliminary frameworks and innovative study designs that can assist clinical rehabilitation researchers in doing so. We argue that researchers who include a direct statement regarding why and to whom a study is relevant and who incorporate considerations of relevance throughout all phases of study design produce more useful research for patients, caregivers, and clinicians, increasing its chance of uptake into practice. Consistent consideration of relevance, particularly to nonacademic audiences, during the conceptualization, study design, presentation, and dissemination of clinical rehabilitation research may promote the uptake of findings by patients, caregivers, and providers.